Neurodevelopmental Disorders (NDDs): Beyond the Clinical Definition and Translational Approach - Stefano Pallanti; Luana Salerno (MDPI AG, 2023)
Neurodevelopmental disorders (NDDs) are complex and heterogeneous disorders that affect the growth and development of the brain and are often associated with impairments in cognitive and motor functions, communication, and adaptive behavior [...]